Influence of sodium citrate supplementation after dehydrating exercise on responses of stress hormones to subsequent endurance cycling time-trial in the heat - Suvi, S.; Mooses, M.; Timpmann, S.; Medijainen, L.; Unt, E.; Ööpik, V. (Medicina, 2019)
Background and objectives: In temperate environments, acute orally induced metabolic alkalosis alleviates exercise stress, as reflected in attenuated stress hormone responses to relatively short-duration exercise bouts. However, it is unknown whether the same phenomenon occurs during prolonged exercise in the heat. This study was undertaken with aim to test the hypothesis that ingestion of an alkalizing substance (sodium citrate; CIT) after dehydrating exercise would decrease blood levels of stress hormones during subsequent 40 km cycling time-trial (TT) in the heat. Materials and Methods: Male non-heat-acclimated athletes (n = 20) lost 4% of body mass by exercising in the heat. Then, during a 16 h recovery period prior to TT in a warm environment (32 °C), participants ate the prescribed food and ingested CIT (600 mg·kg-1) or placebo (PLC) in a double-blind, randomized, crossover manner with 7 days between the two trials. Blood aldosterone, cortisol, prolactin and growth hormone concentrations were measured before and after TT. Results: Total work performed during TT was similar in the two trials (p = 0.716). In CIT compared to PLC trial, lower levels of aldosterone occurred before (72%) and after (39%) TT (p 0.001), and acute response of aldosterone to TT was blunted (29%, p 0.001). Lower cortisol levels in CIT than in PLC trial occurred before (13%, p = 0.039) and after TT (14%, p = 0.001), but there were no between-trial differences in the acute responses of cortisol, prolactin or growth hormone to TT, or in concentrations of prolactin and growth hormone before or after TT (in all cases p > 0.05). Conclusions: Reduced aldosterone and cortisol levels after TT and blunted acute response of aldosterone to TT indicate that CIT ingestion during recovery after dehydrating exercise may alleviate stress during the next hard endurance cycling bout in the heat